1995
DOI: 10.1007/bf01834388
|View full text |Cite
|
Sign up to set email alerts
|

Quality of pooled platelet concentrates prepared from buffy coats and stored in an additive solution after filtration

Abstract: Platelet concentrates prepared from buffy coat were pooled and stored for 6 days after removal of leukocytes by filtration. The platelets were stored in plasma or in an additive solution, Plasmalyte-A. In vitro platelet function was better preserved using Plasmalyte-A than plasma with regard to osmotic reversal and aggregation. No significant differences for the release of platelet markers beta-thromboglobulin, platelet factor 4, or lactate dehydrogenase pre- and post-filtration and storage in plasma or Plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1996
1996
2003
2003

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…As PASIII is identical to PASII, except for the addition of phosphate to the medium, the similarity of results between our study and that of de Wildt‐Eggen et al [13] is not unexpected. It is probable that the degree of platelet activation in PC is related to the composition of the PAS, as cell‐surface CD62P levels in PC stored in a different PAS – Plasmalyte – are not significantly different to those in plasma [29]. The percentage of platelets expressing CD62P was higher in all units stored in PAS compared with plasma, the highest levels being seen with standard PASIII.…”
Section: Discussionmentioning
confidence: 99%
“…As PASIII is identical to PASII, except for the addition of phosphate to the medium, the similarity of results between our study and that of de Wildt‐Eggen et al [13] is not unexpected. It is probable that the degree of platelet activation in PC is related to the composition of the PAS, as cell‐surface CD62P levels in PC stored in a different PAS – Plasmalyte – are not significantly different to those in plasma [29]. The percentage of platelets expressing CD62P was higher in all units stored in PAS compared with plasma, the highest levels being seen with standard PASIII.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies on the use of synthetic storage media confirm the large benefit of acetate in the maintenance of platelet quality during storage [27,28,47,48,58,72], but a minimum plasma carryover of at least 15% seems to be essential for preservation of platelet integrity. With a lower plasma portion, the remaining buffer capacity and glucose levels are not able to allow a successful storage of platelets [46,81], and the requirements for the synthetic medium become very rigorous [58].…”
Section: Metabolismmentioning
confidence: 95%
“…When stored in autologous plasma and in containers with sufficient gas permeability, these two metabolic parameters are stable for at least 5 days, but when balanced salt solutions without adequate fuels or buffer capacity are substituted for the blood plasma, metabolic problems may occur to a variable degree. Several studies have shown the benefit of additive solutions for the storage of PC [28,47,48] provided that a minimum plasma carryover of 15-20% is given. With the introduction of acetatecontaining additive solutions, the energy supply as well as the stability of the pH within the PC were markedly improved [27-29, 58, 81].…”
Section: Mechanisms Of the Storage Lesionmentioning
confidence: 99%